On capacity characteristics of condensers - Zorii, N. V. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We introduce and study a one-parameter family of capacity characteristics of condensers in ℝ p ,p ≥ 3, that contains some known capacities as elements extremal with respect to the parameter. We establish new relations between the capacity characteristics of condensers and sets.